2020
DOI: 10.1016/j.solmat.2020.110406
|View full text |Cite
|
Sign up to set email alerts
|

Strongly enhanced upconversion in trivalent erbium ions by tailored gold nanostructures: Toward high-efficient silicon-based photovoltaics

Abstract: Upconversion of sub-band-gap photons constitutes a promising way for improving the efficiency of silicon-based solar cells beyond the Shockley-Queisser limit. 1500 nm to 980 nm upconversion by trivalent erbium ions is well-suited for this purpose, but the small absorption cross section hinders real-world applications. We employ tailored gold nanostructures to vastly improve the upconversion efficiency in erbium-doped TiO 2 thin films. The nanostructures are found using topology optimization and parameter optim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 34 publications
0
27
0
Order By: Relevance
“…In recent work [28], it was demonstrated that using a refractive index and extinction cross-section-based non-linear material interpolation yielded significantly improved results when designing Au, Ag, and Cu nano-particles for localized field enhancement, with recent applications to enhanced upconversion [29], thermal emission [30], and Raman scattering [31]. This interpolation function avoids artificial resonances in connection with the transition from positive to negative ε values and reads Fig.…”
Section: A Plasmonicsmentioning
confidence: 99%
“…In recent work [28], it was demonstrated that using a refractive index and extinction cross-section-based non-linear material interpolation yielded significantly improved results when designing Au, Ag, and Cu nano-particles for localized field enhancement, with recent applications to enhanced upconversion [29], thermal emission [30], and Raman scattering [31]. This interpolation function avoids artificial resonances in connection with the transition from positive to negative ε values and reads Fig.…”
Section: A Plasmonicsmentioning
confidence: 99%
“…The reader may solve the problem in Eq. (19), using a continuation of the β values, by executing the study named Continuation in the model MetalensCase3.mph. Hereby the field,ξ(r), shown in Fig.…”
Section: Case 3: Filter and Thresholdmentioning
confidence: 99%
“…Besides the above change to the FOM, the optimization problem being solved remains the same as in Eq. (19). The reader may solve the new problem by executing the study named Continuation in the model MetalensCase4.mph.…”
Section: Case 4: Multiple State-equation Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Application of upconversion luminescent nanoparticles composed of lanthanide ions doped inorganic host material as spectrum modifier have attracted great interest due to their outstanding luminescent properties, which are potentially used in laser materials, medical [1] and photovoltaic [2] applications. In recent years, semiconductor metal oxides (TiO 2 , SnO 2 , ZnO, In 2 O 3 ) have been widely used as host materials due to their high thermal and chemical stability, and suitability in many applications such as photocatalysis [3], sensor devices [4], and optical devices [5].…”
Section: Introductionmentioning
confidence: 99%